A numerical study of the basal heave failure mechanism based on groundwater level changes in Bangkok aquifer system - Thatree Deekaoropkun; Avirut Puttiwongrak; Chao, Kuo Chieh; Krit Saowiang; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
The groundwater level in Bangkok aquifer system was subjected to drawdown and recovery during 1960 to present due to the urbanization of Bangkok city. In the meantime, numerous excavation projects were carried out in Bangkok area to serve urbanization. However, groundwater recovery since 1997 creates difficulties in excavation in Bangkok. The one of important design for an excavation in Bangkok area which situated in soft clay deposits region is base stability. The base stability analysis of the excavation in soft clay usually adopts the conventional limit equilibrium method to analyze the stability of the excavations.In this study, comprehensive numerical FEM analyses were carried out to study the efficiency, applicability, and validity of the analytical methods that are widely used in base stability analysis. The comparison between numerical and analytical methods suggest that Terzaghi (1943) method provides overestimating FS against basal heave failure but assumed reasonably accurate failure mechanism, Bjerrum and Eide (1956) method calculates consistent FS but disagree failure surface, and M.F. Chang (2000) method yield reasonably FS calculation and failure behaviors predictions.Moreover, numerical fully coupled flow-deformation analysis with FEM were performed to simulate the effects of groundwater level drawdown and recovery in the Bangkok aquifer system on the Bangkok subsoil condition and simultaneously on the basal heave failure behaviors of the excavations in Bangkok subsoil condition. The analyses results suggested that groundwater level drawdown and recovery in the PD aquifer could induce the pore water pressure, effective stress, and undrained shear strength of the Bangkok subsoil condition to be changed due to the consolidation. The study on the effects of groundwater level changes on the basal heave failure behaviors of the excavations cases in Bangkok subsoil condition revealed that excavations under different groundwater condition could have different basal heave failure behaviors as well as the different factor of safety, where the impact is groundwater level changes is depending on the excavation depth.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Geotechnical and Earth Resources Engineering
Thesis (M. Sc.) - Asian Institute of Technology, 2024
Keywords: Geology -- Thailand -- Bangkok; Groundwater -- Thailand -- Bangkok; Aquifers -- Thailand -- Bangkok